Avaliação do conhecimento social no município de Morrinhos - GO a respeito do Projeto Genoma Humano (Movimenta (ISSN 1984-4298), 2018)
The human genome is the set of all the genetic material contained in chromosomes, present in all our cells. The human genome project is undoubtedly the most audacious project of biology, and intends to have the entire gene sequence of the human species, find their location and determine its function. But Knowledge about the Human Genome Project is restricted to a small portion of the world population is one that most people do not have knowledge or even a clear information about it. These facts this article brings the level of clarity of the population of Morrinhos about what is the human genome project. Respondents were shown to have a prior knowledge about genetic engineering and human genome project, however no detailed theoretical background on the subject.